THE INFLUENCE OF POSYANDU CADRE SERVICE QUALITY ON THE EFFECTIVENESS OF THE NON-COMMUNICABLE DISEASE RISK FACTOR CONTROL PROGRAM IN SUNGAI PINANG VILLAGE, SUNGAI PANDAN SUB-DISTRICT, HULU SUNGAI UTARA REGENCY - Ramona Handayani; Mahdalina Mahdalina (Journal of Development Administrations Thinking Understand: Public and Business Administration (DATU), 2025)
This study reveals several fundamental issues, including the low level of public awareness, limited budget, and the suboptimal use of available facilities and infrastructure. The research aims to analyze the influence of posyandu cadre service quality on the effectiveness of program implementation. A quantitative approach with an associative research type was employed. All questionnaire items were deemed valid, as their correlation values exceeded the critical r-value (more than 0.2732). The research instrument also proved to be reliable, as indicated by a Cronbach’s Alpha value of 0.97. The data were normally distributed based on the Kolmogorov-Smirnov test, with a significance value greater than 0.05. Furthermore, the linearity test showed a significant linear relationship between the independent and dependent variables. The heteroscedasticity test using a scatter plot indicated a data distribution pattern suggestive of heteroscedasticity symptoms. In the hypothesis test, the calculated t-value was 26.718, which was higher than the critical t-value of 2.402 (with 48 degrees of freedom), thus the alternative hypothesis (Ha) was accepted. This finding was supported by the linearity test, which yielded a significance value of 0.000 (< 0.05), indicating a strong linear relationship between the variables studied. Service quality was proven to contribute 94% to program effectiveness, as reflected in the following simple linear regression equation:Y = 5.486 + 1.168X.